The Effectiveness of Bank Recapitalization in Japan - Montgomery, Heather (Universiti Utara Malaysia, 2007)
This study examines the effectiveness of Japanese banking recapitalization policies. Based on the careful reading of individual business revitalization plans submitted by several banks requesting government funds, we identified four primary goals of the capital injection plan: to increase the bank capital ratios; increase lending to avoid a credit crunch; increase the number of write-offs for non-performing loans; and encourage restructuring. Using a panel of individual bank data, we empirically estimated the effectiveness of the policy. Our findings suggest that capital injections are more effective for international banks than for domestic banks. The capital injections do not appear to affect lending to SMEs for either bank type. For international banks however, receipts of injected capital seem to relax the constraint on overall loan growth. The receipt of injected capital strengthens the capital positions of both international and regional banks, but these results do not hold up once we control for possible endogeneity when tested.